2010
DOI: 10.1371/journal.ppat.1000900
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Internalin B Activates Junctional Endocytosis to Accelerate Intestinal Invasion

Abstract: Listeria monocytogenes (Lm) uses InlA to invade the tips of the intestinal villi, a location at which cell extrusion generates a transient defect in epithelial polarity that exposes the receptor for InlA, E-cadherin, on the cell surface. As the dying cell is removed from the epithelium, the surrounding cells reorganize to form a multicellular junction (MCJ) that Lm exploits to find its basolateral receptor and invade. By examining individual infected villi using 3D-confocal imaging, we uncovered a novel role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 130 publications
(160 reference statements)
10
91
0
1
Order By: Relevance
“…It is increasingly appreciated, however, that microbial interactions with the host epithelium and cell-cell junctions are not restricted to mechanical disruption of barrier function (39,41). Mounting evidence illustrates that bacteria can actively modulate other important aspects of junction function, such as altering cell polarity (42)(43)(44) and intracellular signals emanating from the junctions (45)(46)(47). Our findings build importantly on these observations, revealing not only that S. aureus α-toxin does target the junctions but also that α-toxin acts through adherens junctions components to mediate its cytotoxicity.…”
Section: Plekha7 Contributes To the Severity Of Mrsa Skin And Pneumoniamentioning
confidence: 99%
“…It is increasingly appreciated, however, that microbial interactions with the host epithelium and cell-cell junctions are not restricted to mechanical disruption of barrier function (39,41). Mounting evidence illustrates that bacteria can actively modulate other important aspects of junction function, such as altering cell polarity (42)(43)(44) and intracellular signals emanating from the junctions (45)(46)(47). Our findings build importantly on these observations, revealing not only that S. aureus α-toxin does target the junctions but also that α-toxin acts through adherens junctions components to mediate its cytotoxicity.…”
Section: Plekha7 Contributes To the Severity Of Mrsa Skin And Pneumoniamentioning
confidence: 99%
“…3) (Pentecost et al 2006). Of note, infection of wild-type mice intragastrically with a L. monocytogenes strain expressing a modified InlA that binds murine Ecadherin suggested that InlB also participates in bacterial internalization at small intestine villi; experiments in MDCK cells suggest that InlB does not act as an adhesin but rather accelerates bacterial internalization by promoting endocytosis of junctional components (Pentecost et al 2010). It has thus been proposed that InlA provides specificity of adhesion to exposed E-cadherin at the tip of small intestine villi and InlB activates Met to accelerate junction endocytosis and bacterial invasion of enterocytes.…”
Section: Role Of Inla and Inlb In The Traversal Of The Host Barriers mentioning
confidence: 99%
“…This suggests that, in models permissive to both InlA and InlB, InlB-requirement for Lm invasion of Peyer's patch There are apparently conflicting data regarding the role of InlB in the crossing of intestinal barrier: whereas we have repeatedly found no role for InlB in Lm crossing of the intestinal barrier in in vivo models permissive to both InlA-Ecad and InlB-c-Met interactions (Khelef et al, 2006;Disson et al, 2008), it has been reported by others that InlB accelerates invasion at villous tips in an experimental model using murinized InlA (Pentecost et al, 2010) and plays a role at the Peyer's patch level in WT mice (Chiba et al, 2011). Here, we have confirmed these results and revisited their interpretations in light of our new investigations: we compared the infection of murinized InlA (InlA m ) expressing Lm (Wollert et al, 2007) in WT mice (Pentecost et al, 2010) and the infection of WT Lm in KIE16P mice expressing humanized mEcad (Disson et al, 2008) at the villous tip level. Importantly, we have recently demonstrated that InlA m confers to Lm the ability to target both Ecad and Ncad, the latter being accessible on the luminal side of villous M cells (Tsai et al, 2013).…”
Section: Discussionmentioning
confidence: 54%
“…However, Pentecost et al (2010) have reported that InlB plays a role in invading the tip of intestinal villi in WT mice inoculated with Lm expressing a murinized version of InlA (Lm-InlA m ), which interacts with mEcad. Importantly, we have recently shown that Lm-InlA m not only invades cells expressing acc-Ecad, such as GCs, but also targets villous M cells, as a result of the spurious interaction of InlA m with N-cadherin (Ncad), which is luminally accessible at the apical pole of these cells (Tsai et al, 2013).…”
Section: Inlb Is Not Involved In Lm Crossing Of the Intestinal Barriermentioning
confidence: 99%